A pictorial visualization of normal mode vibrations of the fullerene C_60 molecule in terms of vibrations of a hollow sphere - Dunn, Janette L. (American Chemical Society, Division of Chemical Education, 2010)
Understanding the normal mode vibrations of a molecule is important in the analysis of vibrational spectra. However, the complicated 3D motion of large molecules can be difficult to interpret. We show how images of normal modes of the fullerene molecule C60 can be made easier to understand by superimposing them on images of the normal mode vibrations of a thin spherical shell. We describe an interactive demonstration that allows the normal mode to be viewed with or without the shell. The images of the normal modes can be reoriented, and animated to show the vibration. In addition, supporting information includes images of all 174 normal modes of C60 in a common orientation, each of which can be animated. The ideas could be applied to other molecules in which the atoms all lie close to the surface of a sphere.